Perancangan Sistem dan Denah Bazaar Dengan Memanfaatkan Canvas HTML5 Berbasis Website dan Android - Rei Benedict Tirtokusumo; Andreas Handojo; Henry Novianus Palit (Jurnal Infra, 2016)
At present, almost every organizers holds an attractive bazaar due to the growing number of enthusiasts who want to join bazaar. Bazaar can be an alternative place to sell new product and introduce the local product to the general society. Booking booth process in bazaar still using manual system, which tenant fills the order form and then the form is scanned to be sent to the organizer of the event via e-email. Once the booking is received, event organizer has to check and make a registration list of tenants whom will join the bazaar. Therefore there is a need to have an information system to help both eventorganizer and tenant to make a better booking process. Aplication Bazaar based on Android and website intends to help user do all booking process efficiently.Application based on mobile assist tenant in making reservation from fill form until payment order. It helps tenant to search for information about the bazaar which will be held in accordance with bazaar categories of interest and can follow event, so tenant will be easier to get bazaar information. In addition, application based on website helps event organizer to manage the whole process from booking to the payment which received from tenant order, then event organizer can edit event map in order to facilitate tenant when choose a booth at the bazaar.The test results which obatained have two modules, Mobile Application based on Android for tenant and application website for event organizer. Mobile Application can make a booking in bazaar, can get a notification, follow the event, displaying order data. Application website for the event organizer can manage the whole order and payment from tenant, and can edit map event to help tenant make an order. From the test of mobile application that have been done, 50% of respondents rate the app is overall good, and 42% of respondent rate the app overall very good. For Website Application, event organizer has satified with the existing features on the website.